Pengaruh kualitas layanan dan medical expenses terhadap kepuasan pasien pada pusat kesehatan masyarakat (Puskesmas) Cimahi Tengah - Sindrawati, Sindrawati; Muslimah, Elis; Koniah, Koniah; Pratiwi, Merita Gianti; Gumelar, Ikhsan; Zulhazmi, Mohammad Farisan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2022)
This study aimed to analyze the effect of service quality and medical expenses on patient satisfaction at the Community Health Center (Puskesmas) in Central Cimahi, West Java. This research was conducted using quantitative methods with a descriptive verification approach. The population in this study were patients at the Cimahi Tengah Health Center in 2020, and the number of samples taken was 100 respondents. The questionnaire in this study was measured using a Likert scale to determine respondents' perceptions of service quality, medical expenses, and the satisfaction they felt. The data obtained were processed using multiple regression analysis with SPSS 23 software. The results of this study indicate that there is a positive effect of service quality and medical expenses on patient satisfaction at the Cimahi Tengah Health Center. The findings of this study can provide views for managers, doctors, nurses, and health workers, especially those at the Cimahi Tengah Health Center, so that patient satisfaction can be further improved.